2020
DOI: 10.3390/e22050561
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Emergent Order in Far-from-Equilibrium Driven Systems: From Kuramoto Oscillators to Rayleigh–Bénard Convection

Abstract: Soft-matter systems when driven out of equilibrium often give rise to structures that usually lie in between the macroscopic scale of the material and microscopic scale of its constituents. In this paper we review three such systems, the two-dimensional square-lattice Ising model, the Kuramoto model and the Rayleigh–Bénard convection system which when driven out of equilibrium give rise to emergent spatio-temporal order through self-organization. A common feature of these systems is that the entities that self… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Rather, we use this paper as an avenue to present experimental evidence in support of the local-equilibrium assumption in a prototypical driven system, the non-turbulent Rayleigh-Bénard convection at steady-state. This work builds on our previous studies where we have performed extensive thermal analysis of these convective cells, and have shown that the temperature manifold bifurcates into regions of local sources and sinks as macroscopic order emerges [28,29,30,31,32,33]. In this paper, we first show that the temperature distribution profiles of these localized domains that coexist together at a non-equilibrium steady-state exhibit room temperature equilibrium-like statistics.…”
Section: Introductionmentioning
confidence: 56%
“…Rather, we use this paper as an avenue to present experimental evidence in support of the local-equilibrium assumption in a prototypical driven system, the non-turbulent Rayleigh-Bénard convection at steady-state. This work builds on our previous studies where we have performed extensive thermal analysis of these convective cells, and have shown that the temperature manifold bifurcates into regions of local sources and sinks as macroscopic order emerges [28,29,30,31,32,33]. In this paper, we first show that the temperature distribution profiles of these localized domains that coexist together at a non-equilibrium steady-state exhibit room temperature equilibrium-like statistics.…”
Section: Introductionmentioning
confidence: 56%
“…In general, the presence of such randomness models a wide range of collective behaviors observed in diverse out-of-equilibrium systems, characterized by tilted or switching periodic potentials, affected by stochastic fluctuations of temperature, current, or magnetic field, indicates the presence of noise-induced phenomena, such as noise-enhanced stability and resonant activation with different features [32][33][34]. In fact, randomness is not only able to generate disorder, but it may also give rise to new ordered states and induce unexpected dynamical behaviors, which would not be found in the deterministic counterpart of the system such that a mixture of synchronized and unsynchronized oscillators in which some oscillators reach the common frequency and lock themselves in that state before the other, and the evolution of order is inversely related to the fluctuations of the intrinsic oscillators [35,36]. These significant studies show that the underlying frequency structure is critical since it controls the model synchrony transition phases and drastically alters the model's stability aspects and their dimensionality reduction, especially when they are altered by noise.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a linear relationship between surface temperature standard deviation and emergent flux also implies a linear relationship between surface temperature standard deviation and thermodynamic force. We believe that this observation is non-trivial as this emergent thermodynamic force should comply with the second law of thermodynamics and decrease the potential of the system -as indicated by the largest decline during the time evolution of the surface temperature standard deviation, or equivalently lead to an increase in the entropy production during the dissipative process of pattern formation [5,17,[28][29][30].…”
Section: Discussionmentioning
confidence: 99%